Cretaceous ammonite zonation of the Sergipe Basin, northeastern Brazil - Bengtson, Peter; Zucon, Maria Helena; Conceição Santos Sobral, Anderson da (Cretaceous research, 2018)
A biostratigraphic zonation scheme based on ammonites is presented for the Cretaceous of the Sergipe Basin in northeastern Brazil. The marine beds range from the upper Barremian to the Maastrichtian, of which the Aptian-Coniacian and Campanian successions have yielded ammonites. The historical development leading to the current ammonite zonation is illustrated schematically. For each of the 22 biozones, the most important taxa are listed. Correlation with the “standard zonation” for ammonites remains largely tentative as a result of provincialism of the faunas.